The farmer's library - Farrar, Robert Kilby (My University, 1896)
Introduction: Although farming is not one of the three professions, Theology, Law, or Medicine, it is, nevertheless, worthy of a place in this category. In various forms it has never the means, more or less directly, of man’s support ever since his ariston. The art of gaining subsistence by tilling the soil is so easily accomplished that farming has been made the refuge of all who have failed in other vocations of life. Once a farmer, always a farmer has been too much the custom. Farmer’s sons make farmers.
Citation: Farrar, Robert Kilby. The farmer's library. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Farming; Professions; Man; Subsistence; Theses; Manuscripts (documents)